Testing The Effectiveness of Aloe Vera Ethanol Extract Cream on Wound Healing Incision in the Skin of Mice (Mus Musculus) - Dilla Sastri Mara (PT Inovasi Pratama Internasional, 2022)
A wound is an injury to the skin structure of the underlying tissue that may or may not result in a loss of skin integrity. One of the plants used for wound healing is aloe vera ( Aloe vera ). The purpose of this study was to determine the effectiveness and the most effective concentration of aloe vera extract cream for wound healing in mice. This research is experimental research. Because in this study three concentrations of aloe vera extract cream were used 10%, 25%, 50%, and povidone iodine as comparison. From this study, it was found that 10% aloe vera extract cream could heal cuts in mice for 13.2 days. Aloe vera extract cream 25% can heal cuts in mice for 12.6 days. Meanwhile, 50% aloe vera extract cream can heal cuts in mice for 10.6 days. Povidone iodine which was used as a positive control healed cuts on the skin of mice for 12.6 days. The cream base used as a negative control was able to heal cuts in mice for 12.8 days. From this study it can be concluded that the preparation of aloe vera extract cream is effective in healing cuts in mice.